Valuable content marketing how to make quality content your key to success - Jefferson, Sonja; Tanton, Sharon (Kogan Page, 2015)
"The first edition of Valuable Marketing Content provided a clear, straightforward guide on what to write and produce, what type of information to share, and how to share it to get the most effective results. Written for the current business environment, particularly start-ups and consulting companies, this updated second edition offers new ideas, examples, step-by-step action lists, quick tips, and goal-driven chapter summaries to help businesses create compelling, targeted content for their customers"--Provided by publisher.